2022
DOI: 10.1177/11786469221126063
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Profile of Kynurenine Pathway Metabolites in a Rodent Model of Autosomal Recessive Polycystic Kidney Disease

Abstract: Autosomal recessive polycystic kidney disease (ARPKD) is an early onset genetic disorder characterized by numerous renal cysts resulting in end stage renal disease. Our study aimed to determine if metabolic reprogramming and tryptophan (Trp) metabolism via the kynurenine pathway (KP) is a critical dysregulated pathway in PKD. Using the Lewis polycystic kidney (LPK) rat model of PKD and Lewis controls, we profiled temporal trends for KP metabolites in plasma, urine, and kidney tissues from 6- and 12-week-old mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…Similar observations were made by Klawitter et al, who reported correlation between plasma KYNA level, immune activation and CKD severity in patients with autosomal dominant polycystic kidney disease (Klawitter et al 2022). Interestingly, a recent paper by Pires et al on the Lewis polycystic kidney (LPK) rat model not only demonstrated age dependent KYN accumulation in the plasma and the kidney but also showed stimulation of enzymatic Trp degradation, namely through increased activity of KATs (Pires et al 2022). Since KYN and its metabolites are classi ed as uremic toxins, inhibitory effect of brates on KYNA synthesis should be considered as novel mechanism of kidney protection.…”
Section: Discussionsupporting
confidence: 72%
“…Similar observations were made by Klawitter et al, who reported correlation between plasma KYNA level, immune activation and CKD severity in patients with autosomal dominant polycystic kidney disease (Klawitter et al 2022). Interestingly, a recent paper by Pires et al on the Lewis polycystic kidney (LPK) rat model not only demonstrated age dependent KYN accumulation in the plasma and the kidney but also showed stimulation of enzymatic Trp degradation, namely through increased activity of KATs (Pires et al 2022). Since KYN and its metabolites are classi ed as uremic toxins, inhibitory effect of brates on KYNA synthesis should be considered as novel mechanism of kidney protection.…”
Section: Discussionsupporting
confidence: 72%
“…The circulating levels of KYN, KYNA and other kynurenines are related to the severity of diabetic CKD [30,31]. Similarly, the correlation between plasma KYNA levels, immune system activation and CKD severity was described in animal models and in patients with autosomal dominant polycystic kidney disease (ADPKD) [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The activity of KP enzymes was calculated indirectly by the determination of product-to-substrate ratios 36 . KYN/TRP ratio, a clinical index of TDO/IDO1 activity (Fig.…”
Section: Serum Kynurenine Pathway (Kp) Metabolites and Enzyme Activit...mentioning
confidence: 99%